2001
DOI: 10.2337/diabetes.50.10.2296
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone Not Only Increases GLUT4 but Also Induces Its Translocation in Rat Adipocytes

Abstract: Thiazolidinediones, insulin-sensitizing agents, have been reported to increase glucose uptake along with the expression of glucose transporters in adipocytes and cardiomyocytes. Recently, we have further suggested that the translocation of GLUT4 is stimulated by thiazolidinediones in L6 myocytes. However, the direct effects of thiazolidinediones on translocation of glucose transporters have not yet been determined. In this study, using hemagglutinin epitope-tagged GLUT4 (GLUT4-HA), we provide direct evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
3
14
1
Order By: Relevance
“…In support of this, the rosiglitazoneinduced effects on GLUT4 required several days of treatment. In contrast, troglitazone has been shown to largely alter cell surface GLUT4 levels in muscle and fat cells within 15 and 24 hours of treatment, respectively [30,31]. Troglitazone concentrations that were found to increase cell surface GLUT4 levels in these studies were much higher than the concentrations of rosiglitazone we found to be effective, but this correlates well with the lower affinity of troglitazone for PPARγ [32,33].…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…In support of this, the rosiglitazoneinduced effects on GLUT4 required several days of treatment. In contrast, troglitazone has been shown to largely alter cell surface GLUT4 levels in muscle and fat cells within 15 and 24 hours of treatment, respectively [30,31]. Troglitazone concentrations that were found to increase cell surface GLUT4 levels in these studies were much higher than the concentrations of rosiglitazone we found to be effective, but this correlates well with the lower affinity of troglitazone for PPARγ [32,33].…”
Section: Discussioncontrasting
confidence: 50%
“…Troglitazone concentrations that were found to increase cell surface GLUT4 levels in these studies were much higher than the concentrations of rosiglitazone we found to be effective, but this correlates well with the lower affinity of troglitazone for PPARγ [32,33]. Neither in muscle cells [30] nor in adipocytes [31,34] (Fig. 3A, C) were the effects of glitazones and high concentrations of insulin additive.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…PPAR-γ activation leads to stimulated glucose uptake, storage of triglycerides and production of adiponectin. It also induces increased GLUT-4 mRNA levels in adipocytes [31]. Muscle and adipose tissue contain at least two kinds of glucose transporter, GLUT-1 and GLUT-4, among which GLUT-4 is an important insulin regulator [32].…”
Section: Discussionmentioning
confidence: 99%